Normative Juridical Aspects in Customary-Based Environmental Management in The Rokan Hulu Area - Ridho Harapan Bunda; Hardianto; Welven Aida; Lusi Dwi Septiani (Indonesian Journal of Law and Justice, 2025)
This study examines the role of customary law in environmental management in the Rokan Hulu Area and its disharmony with state law. Customary law has strong ecological value through practices such as prohibition loopholes, customary forest management, and restrictions on resource exploitation. However, its implementation is often hampered by formal policies that do not consider the customary rights of indigenous peoples, especially in the licensing process. Through normative juridical analysis with legislative and conceptual approaches, this study finds that the integration of customary law and state law needs to be strengthened through ecological justice approaches and participatory mechanisms. The results of the study confirm that customary law has the potential to become a model of sustainable environmental management if supported by operational regulations, strengthening customary institutions, and collaboration between the government, indigenous peoples, and academics. These findings are relevant for the development of national environmental policies and the achievement of sustainable development goals.